Effect of graphene modified semi‐conductive shielding layer on space charge accumulation in insulation layer for high‐voltage direct current cable. (12th November 2021) - Li, Guochang; Li, Xuejing; Zhang, Fan; Liang, Xiaojian; Liu, Mingyue; Wei, Yanhui; Li, Shengtao; Hao, Chuncheng; Lei, Qingquan
Abstract: Space charge accumulation in the insulation layer of high‐voltage direct current (HVDC) cable is one of the key factors restricting the development of HVDC cable. The inner semi‐conductive layer as an important structure of cable will affect the charge accumulation characteristics in the insulation layer. This work intends to explore the method of modifying the semi‐conductive layer with graphene, to suppress charge accumulation in the insulation layer. First, the semi‐conductive layer with different contents of Graphene (G) and carbon black (CB) are prepared. Second, the morphology and surface roughness of the cross section are analysed. Further, the effects of the semi‐conductive layer on space charge accumulation of the insulation layer are studied by pulsed electro‐acoustic method and thermal stimulation depolarisation current method. The experimental results show that a moderate amount of graphene replacing CB can effectively reduce charge accumulation in the insulation layer and inhibit positive temperature coefficient (PTC) effect at the same time. The surface roughness of specimens decreases with the increase of G content from 0 to 3 phr (parts per hundreds of resin), when the CB content decreases from 25 to 10 phr, the surface roughness of specimen increases. The resistivity test shows that doping G can significantly inhibit the PTC effect of the semi‐conductive layer. The volume resistivity of the semi‐conductive layer decreases with the increase of G content and CB content. In addition, charge accumulation of the insulation layer rises and then drops under the action of the semi‐conductive layer.